POLIMERISASI o-TOLUIDIN DALAM FASA AQUEOUS DAN PENGEMBANGANNYA UNTUK MEMBUAT FILM POLI-o-TOLUIDIN SECARA in situ - W., Endang Asijati; Susanto, Dieky; Tockary, Theofilus A; Sabarinah, Yanti (UI Scholars Hub, 2006)
O-toluidine Polymerization in Aqueous Phase and Its Development to Produce In Situ Poly-o-toluidine Films. Polymerization parameters of aqueous phase which have an effect to polymer film were studied in order to establish indirect control of film fabrication by means of controlling the parameters of aqueous phase. Among the parameters studied are the concentration of HCl, APS/o-toluidine ratio, polymerization duration, and temperature. HCl concentration was found to be optimum at the excess value of 1.0M, whereas ratio of APS/o-toluidine at 1.25. Polymerization duration was found of having an effect to both stability and thickness. As a rule, longer duration of polymerization leads to a thicker and more stablized polymer film. Temperature was found to be a parameter that have a defining role in the control of film thickness. Despite of the rather semi quantitative nature of the data, the results show a clear indication that indirect control is possible for in situ method of o-toluidin film fabrication.